Cardiopulmonary resuscitation knowledge and skills among school teachers in Xinjiang, China: a cross-sectional survey - Ma, Jin; Kuai, Liuniu; Zhu, Xiaolong; Tang, Qi; Liu, Shifang; Zhou, Weiwei (Frontiers in Public Health, 2025)
BackgroundCardiopulmonary resuscitation (CPR) is a critical, life-saving intervention that is especially important in school settings. This study assessed the levels of CPR knowledge, training, and rescue willingness among school teachers in Xinjiang, China.MethodsWe conducted an online cross-sectional survey among 368 full-time teachers across primary, middle, and high schools (May–June 2025). A composite CPR readiness score (0–100) combined self-reported knowledge, training (formal or self-study vs. none), four core technical items (golden time, compression location, depth, rate), and rescue willingness. Group differences were assessed by Kruskal–Wallis with FDR-adjusted Mann–Whitney post hoc tests; categorical associations used chi-square with Cramer’s V; multivariable correlates of readiness were examined by OLS with robust SEs.ResultsOverall, 37.0% were trained (self-study or formal); 10.9% reported “very clear” knowledge. Technical knowledge accuracy was uneven: compression location 78.0%, golden time within 4 min 68.5%, compression rate 100–120/min 44.8%, and depth 5–6 cm 39.7%. Mean readiness was 55.7 ± 17.4 (95% CI: 53.9–57.4) and was higher in trained than untrained teachers (69.8 ± 13.3 vs. 47.4 ± 13.8; p < 0.0001). Readiness differed by age (p = 0.019; lower in 46–60 years) and ethnicity (Han 57.2 ± 16.6 vs. other minorities 52.8 ± 18.5; p = 0.027), and was higher among those aware of AED locations (69.3 ± 16.0; p < 0.0001). In OLS, training (+20.39 points [95% CI: 17.54–23.23]; p < 0.0001), AED awareness (+8.35 [4.09–12.62]; p = 0.000124), and often worrying about emergencies (+12.09 [4.37–19.81]; p = 0.002) were independent positive correlates; male sex (−3.54 [−6.91 to −0.18]; p = 0.039) and other minority ethnicity (−5.57 [−8.99 to −2.14]; p = 0.001) were negative.ConclusionThe findings demonstrate an urgent need for systematic and culturally adapted CPR training programs among school teachers in Xinjiang, China.